Kassationer på ett livsmedelslager - Effektivisering och kvalitetssäkring av processen för intern kassation i enlighet med Lean Production - Almstedt, Jan; Andersson, Johanna (My University, 2013)
Today's fierce competition means that companies constantly must develop their business and internal processes. Focus on processes and continuous improvement is something that characterizes Lean Production which ICA logistics are applying with their concept Leading Logistics. Standardized routines for handling damaged gods were insufficient at the ICA distribution center in Kungälv. Handling and registration of damaged gods were not performed uniformly, resulting in problems with controlling and monitoring the process. The purpose of this thesis was to analyze and make recommendations how the process of internal handling of damaged gods could be improved. Therefore a comprehensive understanding was needed of the entire material flow through the warehouse and important quality aspects such as product safety and delivery reliability. The methods used are literature reviews, interviews and observations to produce a comprehensive process mapping of the current situation at the distribution center. Causes to why damaged gods occur were identified through process mapping and improvement meetings. Finally all input was analyzed which resulted in recommendations on how the process could be improved. Several unnecessary steps have been identified in the process of handling damaged goods and that the registration procedure sometimes resulted in incorrect inventory levels. Another problem was that several people make individual decisions regarding measures for damaged goods depending on how it occurred and was discovered. Important reasons identified to cause damage to the goods were poor packaging and rough handling. Another important aspect was that damages often became more severe in the actual handling of damaged goods. To improve the process of internal handling of damaged gods, ICA was recommended to take on a more proactive approach such as improving poor packaging. ICA was also recommended to prioritize early measures by restoring more goods directly when damage occurs. Quality should be seen as an integrated part of the core process and everyone should be involved and feel responsible for the quality. The report is written in Swedish.
Keywords: Produktion; Övrig industriell teknik och ekonomi; Production; Other industrial engineering and economics